AWS certified developer associate (DVA-C02). (Pearson, 2023)
18+ Hours of Video Instruction Prepare for the all-new AWS Certified Developer Associate DVA-C02 exam! Overview: AWS Certified Developer - Associate (DVA-C02) is your complete study resource covering all the objectives in the DVA-C02 exam. Throughout this course, you will explore a multitude of AWS services, dive into hands-on exercises, and learn best practices for developing, deploying, and debugging cloud-based applications on AWS. You will also navigate the vast landscape of AWS SDKs and APIs and understand how to leverage them effectively. With expansive coverage of all topics contained in the Exam Guide this course not only covers all the objectives in the exam; it also provides hands-on and in-depth demos throughout so you can see AWS in action and learn real-world skills. This course takes a per-domain approach with an understanding that the prerequisite service-level basics are already understood. What this course offers: Coverage of all key AWS the development services Insights into how to develop, deploy, and debug cloud-based applications using AWS Full preparation for the AWS Certified Developer - Associate (DVA-C02) exam Related learning: Sign up for live training on Certified AWS Developer Associate (DVA-C02) Crash Course with Nick Garner Topics Include: An overview of the course and AWS developer foundations starts at the very beginning by understanding "the cloud" - its concept, significance, and why it's the cornerstone of modern technology infrastructure. Dive into the different level of AWS certifications that will benefit your career and your AWS learning journey. Security is a crucial part of the program. It will focus on fundamental security concepts, authentication, authorization, access control, encryption and managing sensitive data in code. Development with AWS Services covers everything from developing code for applications hosted on AWS to utilizing AWS's vast array of services for application integration. Deployment provides you with the knowledge and skills necessary to effectively deploy applications on AWS. Explore the world of containers in AWS, application artifacts for AWS deployment and understand automating deployment. Troubleshooting and Optimization will equip you with the tools and techniques necessary for effective problem-solving and performance optimization within the AWS environment. About the Instructor: Nick Garner, CCIE #17871, is a Senior Solutions Architect with Denali Advanced Integration as well as a co-founder of an IoT AgTech company. Previously he was a Solutions Integration Architect for Cisco Systems. He was with Cisco Advanced Services for 10 years, supporting customers in both transactional and subscription engagements. He has deployed and supported large-scale data center designs for prominent clients in the San Francisco Bay area. Skill Level: Intermediate/Advanced Learn How To: Use and interact with AWS as a developer Apply architect applications for deployment in the AWS public cloud Refactor applications to use existing AWS services Understand the AWS services commonly used for cloud application development Course Requirement: It is recommended to have AWS Cloud Practitioner certification or equivalent knowledge (This course will not cover the basics of fundamental services such as EC2, VPC, and S3.) Who Should Take This Course: You are a certification exam candidate seeking to hone your skills on exam topics You are interested in taking your AWS developer skills to the next level About Pearson Video Training: Pearson publishes expert-led video tutorials covering a wide selection of technology topics designed to teach you the skills you need to succeed. These professional and personal technology videos feature world-leading author instructors published by your trusted technology brands: Addison-Wesley, Cisco Press, Pearson IT Certification, Sams, and Que Topics include: IT Certification, Network Security, Cisco Technology, Programming, Web Development, Mobile Development, and more. Learn more about Pearson Video training at http://www.informit.com/video.